Analysis of Maintenance Management Model on Refrigerator System on Ship - Kundori, Kundori; Khamdilah, Ali; Imanto, Frenki (Dinamika Bahari, 2025)
One type of auxiliary machinery on the ship is a refrigerator systemthat is used to store food supplies to keep them in fresh condition and not quickly damaged or rotten. The purpose of this study is to provide an analysis of the maintenance management model on the refrigerator system so that it can function optimally and predict the possibility of existing damage. The method used is mix method research by combining quantitative and qualitative designs to provide an overview of the problems and solutions provided to the refrigerator system. The results show that the Filter Dryer has the highest damage rate (25%) and the lowest MTBF (864 hours). The discharge pressure has increased from the standard provisions of 250, but in reality it rose to 275, so that it has a deviation of +10%. The discharge pressure deviation indicates a potential problem with the compressor. Limited spare parts inventory is often a complaint of the chief engineer in carrying out maintenance of refrigerator system. The impact of this research shows that the existing maintenance program needs to be restructured. This restructuring could include rescheduling maintenance activities, allocating resources more effectively, as well as implementing a risk- or condition-based approach to reduce downtime and improve efficiency.